Current status and perspectives on recycling of end-of-life battery of electric vehicle in Korea (Republic of). (1st April 2020) - Choi, Yong; Rhee, Seung-Whee
Highlights: Explain recycling management and technology on end-of-life battery of EV in Korea. Propose the new recycling scheme for end-of-life battery of EV in Korea. Suggest the recirculation flow and safety management of end-of-life battery of EV. Suggest a new initiative for end-of-life battery of EV in the Basel Convention. Abstract: The trend of the market of electric vehicles (EVs) in Korea is increasing because of reduction in heavy fine dust and economic benefit for purchasing EVs. With increasing number of EVs, the recycling of end-of-life battery of EVs is important to recover valuable metals such as Li and Co etc. and to control hazardous substances such as Pb, Cd and Cu. The current status on recycling policy and recycling technology of end-of-life battery of EV was explained in several countries including China, Europe, and Korea. It is necessary to immediately prepare the regulation on the storage, transportation and recycling of end-of-life battery of EV in Korea because of the safety management of end-of-life battery of EV. The new recycling scheme for the management of end-of-life batteries of EV by EPR system is proposed to secure recycling and stability because primary battery in internal combustion engine (ICE) vehicles is managed by the EPR system in Korea. For recycling of end-of-life battery of EVs, the technologies and the recycling level in Korea were compared with other countries. To develop the technical guidelines for the recycling of end-of-life battery of EV, it is proposed to set up an international committee on the recycling of end-of-life battery of EV as a new initiative in the Basel Convention.